Antimicrobial coated implants in trauma and orthopaedics–A clinical review and risk-benefit analysis. Issue 3 (March 2017) - Alt, Volker
Abstract: Implant-associated infections remain a major issue in orthopaedics and antimicrobial functionalization of the implant surface by antibiotics or other anti-infective agents have gained interest. The goal of this article is to identify antimicrobial coatings, for which clinical data are available and to review their clinical need, safety profile, and their efficacy to reduce infection rates. PubMed database of the National Library of Medicine was searched for clinical studies on antimicrobial coated implants for internal fracture fixation devices and endoprostheses for bone surgery, for which study design, level of evidence, biocompatibility, development of resistance, and effectiveness to reduce infection rates were analyzed. Four different coating technologies were identified: gentamicin poly(d, l -lactide) coating for tibia nails, one high (MUTARS ® ) and one low amount silver (Agluna) technology for tumor endoprostheses, and one povidone-iodine coating for titanium implants. There was a total of 9 published studies with 435 patients, of which 7 studies were case series (level IV evidence) and 2 studies were case control studies (level III evidence). All technologies were reported with good systemic and local biocompatibility, except the development of local argyria with blue to bluish grey skin discoloration after the use of silver MUTARS ® megaendoprostheses. For the local use of gentamicin, there is contradictory data on the risk of emergence of gentamicin-resistance strains, a risk that does not seem to exist for silver and iodine based technologies. Regarding reduction of infection rates, one case control study showed a significant reduction of infection rates by Agluna silver coated tumor endoprostheses. Based on socio-economic data, there is a strong need for improvement of infection prevention and treatment strategies, including implant coatings, in fracture care, primary and revision arthroplasty, and bone tumor surgery. The reviewed gentamicin, silver Agluna, and povidone-iodine technologies have shown a good risk benefit ratio for patients. Further data from randomized control trials are desirable, although this will remain challenging in the context of infection prevention due to the required large sample size of such studies.